2015
DOI: 10.3390/md13074270
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin from Irish Brown Seaweeds Ascophyllum nodosum and Laminaria hyperborea: Ultrasound Assisted Extraction, Characterization and Bioactivity

Abstract: Ultrasound assisted extraction (UAE), purification, characterization and antioxidant activity of laminarin from Irish brown seaweeds Ascophyllum nodosum and Laminarina hyperborea were investigated. UAE was carried out using 60% ultrasonic power amplitude and 0.1 M hydrochloric acid for 15 min. Separately, solid-liquid extraction was carried in an orbital shaker using 0.1 M hydrochloric acid at 70 °C for 2.5 h. UAE with hydrochloric acid resulted in the highest concentration of laminarin, 5.82% and 6.24% on dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
132
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(138 citation statements)
references
References 28 publications
4
132
2
Order By: Relevance
“…Improved yield achieved by UAE in comparison to CE is attributed to the bubble cavitation phenomenon generated by ultrasonic waves [75], that was previously observed in fucoidan extraction from Sargassum witghtii [70], Undaria pinnatifida [76] and laminarin extraction from A. nodosum and Laminaria hyperborean [75]. No statistical difference between UAE and CE was reported in fucoidan extraction from N. zanardinii [64] and Fucus evanescens [77], while Okolie et al [65] reported significantly higher yield by CE (11.9%) than by UAE (4.56%) and also no statistical differences between UAE, MAE and EAE.…”
Section: Ultrasound Assisted Extraction (Uae)mentioning
confidence: 97%
“…Improved yield achieved by UAE in comparison to CE is attributed to the bubble cavitation phenomenon generated by ultrasonic waves [75], that was previously observed in fucoidan extraction from Sargassum witghtii [70], Undaria pinnatifida [76] and laminarin extraction from A. nodosum and Laminaria hyperborean [75]. No statistical difference between UAE and CE was reported in fucoidan extraction from N. zanardinii [64] and Fucus evanescens [77], while Okolie et al [65] reported significantly higher yield by CE (11.9%) than by UAE (4.56%) and also no statistical differences between UAE, MAE and EAE.…”
Section: Ultrasound Assisted Extraction (Uae)mentioning
confidence: 97%
“…They are located in cell vacuoles, constitute about 35% dry weight of brown seaweed, and also serve as storage polysaccharides (Kadam, Tiwari, Alvarez, & Donnell, ; O'Sullivan et al, ). Studies on laminarin have shown promising results in its antibacterial, immunomodulating, antioxidative, and anticoagulant properties (Kadam et al, ; Zhang & Row, ). Interestingly, γ‐radiated degradation of laminarin showed increased antioxidant activity and inhibition of melanin synthesis when compared to non‐irradiated laminarin (Choi, Kim, Kim, & Lee, ).…”
Section: Brown Seaweed Polysaccharidesmentioning
confidence: 99%
“…The UAE method uses sound waves migrating through a medium inducing pressure variations and creating small vacuum bubbles or voids which collapse violently (cavitation) resulting localized pressure and heat which helps to extract polysaccharides (Kadam et al, ). Comparing the efficiency of UAE with MAE and CCE, Kadam et al () discovered that extraction with ultrasound‐assisted technology (10.79%) gave better yield when compared to MAE (9.56%) and CSE (4.67%) in lesser time (Kadam et al, ; Ying, Han, & Li, ). However, high energy input and pressure required for UAE and MAE could be detrimental, as they have been associated with cleavage of sulfate esters.…”
Section: Brown Seaweed Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This environmentally benign and cost effective method has successfully extracted highly purified fibrils/nanofibrils from cellulosic materials [81,110]. Although UAE method has been utilized in extraction of bioactive compounds from several marine algae or even non-hydrocolloids materials [81,94,95,111,112]. Still, these were limited studies regarding extraction of seaweed hydrocolloids with this green method.…”
Section: Ultrasound-assisted Extraction (Uae)mentioning
confidence: 99%